Improved ruminant genetics: Implementation guidance for policymakers and investors - Haas, Yvette de; Davis, Steve; Reisinger, Andy; Richards, Meryl B.; Difford, Gareth; Lassen, Jan (2016)
Genetics makes use of natural variation among animals. Selecting preferred animals as parents can yield permanent and cumulative improvements in the population. More efficient animals can greatly reduce greenhouse gas emissions and feed costs. Breeding, including cross-breeding between indigenous and imported species, can also improve resilience to diseases and heat stress and increase reproductive performance.